DINAMIKA PSIKOLOGIS PELAKU PERKAWINAN ANTARETNIS Manifestasi dan Dinamika Interdependensi pada Relasi Perkawinan Perempuan Tionghoa dengan Laki-laki Jawa - , JONY EKO YULIANTO ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study found that Chinese womenâs orientation when looking for husband are more leaning toward personal qualities rather than ethnicity. This is contradictory with their parentsâ orientation that prioritized cultural aspect, thus strongly encourage their children toward homogamy. This orientation difference caused Javanese and Chinese inter-ethnic marriage tends to have conflicting background. Javanese and Chinese ethnicity both emphasize the importance of social harmony in their relations. Does it exist in the marriage relation of Chinese women and Javanese man? This study was conducted by applying qualitative method with phenomenology approach on four married couples in Yogyakarta. The results show that interdependence manifestation in interethnic marriage includes identity establishment, the use of power, and the utilization of resources. Identity establishment consist of fused identity, layered identity, attributed identity, and valuefocused identity. The use of power existed in variations of hierarchy, domination, and versatile. The use of resource showed three variations of communal-sharing, transaction, and domination. Interdependent dynamics between husband and wife manifest in interpersonal level which emphasizes the role of trust and distrust, intrapersonal level which is expressed in affection toward spouse, suprapersonal level which is voiced in the role of trust toward transcendental agents, and intergroup level which is pointed to role of metarelational model of extended family.